Plant-derived isoprenoid sweeteners: recent progress in biosynthetic gene discovery and perspectives on microbial production. Issue 6 (3rd June 2018) - Seki, Hikaru; Tamura, Keita; Muranaka, Toshiya
Abstract: Increased public awareness of negative health effects associated with excess sugar consumption has triggered increasing interest in plant-derived natural sweeteners. Steviol glycosides are a group of highly sweet diterpene glycosides contained in the leaves of stevia ( Stevia rebaudiana ). Mogrosides, extracted from monk fruit ( Siraitia grosvenorii ), are a group of cucurbitane-type triterpenoid glycosides. Glycyrrhizin is an oleanane-type triterpenoid glycoside derived from the underground parts of Glycyrrhiza plants (licorice). This review focuses on the natural isoprenoid sweetening agents steviol glycosides, mogrosides, and glycyrrhizin, and describes recent progress in gene discovery and elucidation of the catalytic functions of their biosynthetic enzymes. Recently, remarkable progress has been made in engineering the production of various plant-specialized metabolites in microbial hosts such as Saccharomyces cerevisiae via the introduction of biosynthetic enzyme genes. Perspectives on the microbial production of plant-derived natural sweeteners are also discussed. Abstract: : Three well-known non-nutritive natural sweeteners, steviol glycosides, mogrosides and glycyrrhizin, are plant-derived isoprenoids.